Classification of entrepreneurial and management capabilities in micro, small and medium-sised enterprises - López Lira, Nidia; Teja Gutiérrez, Rebeca; Loera Suárez, Verónica (2021)
This research tries to make a contribution to the process of characterization and classification of the entrepreneurial and management capabilities which are useful to ensure the operation and permanence in the market of those MSMEs related to traditional technology in developing countries and located in places once regarded as emerging.